Antimicrobial Sales Comparison before and after the Implementation of Nationwide Restriction Policy in Saudi Arabia - Sulaiman M. Alajel; Khaloud O. Alzahrani; Amal A. Almohisen; Meshael M. Alrasheed; Salwa M. Almomen (MDPI AG, 2023)
Antimicrobial dispensing without a prescription has been identified as a significant contributor to the burgeoning crisis of antimicrobial resistance. To combat this, the Saudi Ministry of Health introduced a stringent antimicrobial restriction policy in mid-2018, mandating prescriptions for all antimicrobial drug dispensations at pharmacies. Therefore, this study aimed to assess the immediate impact of this policy on retail antimicrobial sales. To do so, we analyzed annual sales data from 2017 to 2019 sourced from the IQVIA-MIDAS® database, which included a range of antimicrobials, such as antibiotics, antifungals, and other related agents. The analysis revealed a notable reduction in overall antimicrobial sales by 23.2%, decreasing from 818.9 million SAR in 2017 to 648.4 million SAR in 2019. While the Wilcoxon signed-rank test indicated a statistically significant median reduction in total antimicrobial sales post-policy implementation (p = 0.0397), it is important to acknowledge that the long-term effects and adherence to the policy require further investigation. Notably, sales of amoxicillin dropped by 70% in 2019 compared to 2017, contributing largely to the decline. Conversely, a continuous increase in sales of some antimicrobial drugs following the restriction policy was observed, led by amoxicillin/clavulanic acid. Our data support the implementation of antimicrobial restriction measures as an effective means of controlling excessive antimicrobial sales and dispensing without prescriptions.